Study on Polymer Modified Self-Compacting Concrete Used for Repair of Concrete - Kong, Xiangzhi; Zhang, Sijia; Ji, Guojin; Ji, Tao; Liu, Yanxia (Asian Journal of Chemistry, 2014)
This paper developed a polymer modified self-compacting concrete (PMSCC) by using non-air entraining acrylic latex, which is suitable for the replacement of old concrete. Test results show that polymer modified self-compacting concrete has good workability and stability and can achieve self-compacted without any vibration. Its slump flow is greater than 650 mm. Hardened concrete has the features of “low modulus of elasticity, high anti-crack ability and good durability”. The simulation test shows that the interfacial bond strength between new and old concrete is higher than 1.56 MPa without any adhesives.